2018
DOI: 10.1371/journal.pone.0196011
|View full text |Cite
|
Sign up to set email alerts
|

CD44-mediated hyaluronan binding marks proliferating hematopoietic progenitor cells and promotes bone marrow engraftment

Abstract: CD44 is a widely expressed cell adhesion molecule that binds to the extracellular matrix component, hyaluronan. However, this interaction is not constitutive in most immune cells at steady state, as the ability of CD44 to engage hyaluronan is highly regulated. While activated T cells and macrophages gain the ability to bind hyaluronan by CD44, the status in other immune cells is less studied. Here we found a percentage of murine eosinophils, natural killer and natural killer T cells were capable of interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…This result indicates that CD44 regulation may occur at the transcriptional level contributing to the early infection event However, how GATA-3 regulates HSC remains to be determined According to literature, GATA-3 is dispensable for HSC regulation and generation of early T cells [ 61 , 62 ]. It has been suggested that CD44 acts as an early marker of differentiation on immature cells CD34 + and supports HSC survival and maintenance of proliferating hematopoietic progenitor cells [ 63 , 64 , 65 ]. We observed a longitudinal increase in the CD44 rate among CD133 and CD34 cells from days 2–14 (Supplementary Figure S5D).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that CD44 regulation may occur at the transcriptional level contributing to the early infection event However, how GATA-3 regulates HSC remains to be determined According to literature, GATA-3 is dispensable for HSC regulation and generation of early T cells [ 61 , 62 ]. It has been suggested that CD44 acts as an early marker of differentiation on immature cells CD34 + and supports HSC survival and maintenance of proliferating hematopoietic progenitor cells [ 63 , 64 , 65 ]. We observed a longitudinal increase in the CD44 rate among CD133 and CD34 cells from days 2–14 (Supplementary Figure S5D).…”
Section: Discussionmentioning
confidence: 99%
“…CD44, a receptor for the extracellular matrix component hyaluronan, is a widely expressed cell adhesion molecule (56). CD44 plays a vital role in different events involved in the inflammatory process and in several neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that exogenous TSG-6 supplementation can improve hematopoietic progenitor cell function after cigarette smoke-induced myelosupression [16] and alter bone marrow stromal cell differentiation [26] , [27] , respectively. Additionally, a recent study revealed that CD44-HA binding interactions promote bone marrow progenitor proliferation and increase engraftment following irradiation [28] . Taken together, these findings emphasize the need for future studies to investigate the potential contributions of TSG-6 and HC-HA in the bone marrow during systemic inflammatory conditions that stress and mobilize the bone marrow compartment.…”
Section: Discussionmentioning
confidence: 99%